Scleral buckle surgery in Ghana: a decade comparison of the anatomic and visual outcome - Braimah IZ (Dove Medical Press, 2018)
Imoro Z Braimah,1,2 Stephen Akafo,1,2 Jay Chhablani3 1Department of Surgery, School of Medicine and Dentistry, College of Health Sciences, University of Ghana, Accra, Ghana; 2Eye Centre, Korle Bu Teaching Hospital, Accra, Ghana; 3Srimati Kanuri Santhamma Centre for Vitreo-Retinal Diseases, KAR Campus, L V Prasad Eye Institute, Hyderabad, Telangana, India Purpose: To compare the anatomic and visual outcome of scleral buckle (SB) surgery in Korle Bu Teaching Hospital between 2002 and 2005 and 2011 and 2014. Materials and methods: In this retrospective comparative study, the medical records of patients who have undergone SB for rhegmatogenous retinal detachment from January 2002 to December 2005 (group A) and from January 2011 to December 2014 (group B) in Korle Bu Teaching Hospital were examined. The clinical history, surgical techniques, and outcomes of treatment were analyzed. The main outcome measures were primary anatomic success (retina reattached for at least 3 months postoperatively after a single procedure), overall anatomic success (combined primary anatomic success and success following revision of SB with at least 3 months follow-up), mean postoperative best-corrected visual acuity (BCVA), and complications. Results: One hundred fifty-eight eyes (71 eyes in group A and 87 eyes in group B) were treated with SB in this study. The mean duration of rhegmatogenous retinal detachment was 105.5 days. Thirty-four (21.8%) of fellow eyes had BCVA worse than 6/60 at presentation. The primary anatomic success was comparable between the two groups; 70% in group A and 67.9% in group B (P=0.79). The overall anatomic success was also comparable between the two groups (76.7% in group A vs 79.8% in group B) (P=0.788). The mean postoperative BCVA in logMAR was significantly better than the mean preoperative BCVA (P<0.0001). Group B had significantly better mean BCVA (P=0.002) and longer duration of follow-up (P<0.0001) compared with group A at the last follow-up visit. Conclusion: The anatomic success of SB between the two time periods was comparable. A longer postoperative duration of follow-up was associated with a better visual outcome after SB. Keywords: rhegmatogenous retinal detachment, scleral buckle surgery, laser retinopexy, cryotherapy, Ghana